Young people's labour market patterns and later mental health: A sequence analysis exploring the role of region of origin for young people's labour market trajectories and mental health - Anna Brydsten; Agneta Cederström; Mikael Rostila (Elsevier, 2020)
Background: This study used Swedish longitudinal register data to identify clusters of trajectories in labour market positions from young adulthood to mid-life, analyse the trajectory cluster composition regarding region of origin, and to examine if the trajectories was associated with mid-life mental ill health. Method: A cohort of 98 634 individuals (at age 20, 1998) were followed yearly across 18 years, of whom 23.4% were foreign-born or second-generation migrants. Sequence Analysis with Hierarchical Cluster Analysis was used to map individual labour market trajectories (age 20-37) and identify clusters of trajectories, and logistic regression to assess the association between trajectories and mental ill health in mid-life (age 36 to 38). Labour market states were constructed by main source of income, while mental health was operationalised as hospital admission for psychiatric care or receiving a psychiatric diagnosis at a health centre. Early-life course factors and previous health status was included as covariates. Results: Four clusters of trajectories were identified, separately for women and men, reflecting a rapid labour market entry with stable employment (T1), higher education into stable employment (T2), turbulence with several transitions between states (T3), and turbulence into labour market exclusion (T4). Migrants and second-generation migrants were more often found in trajectory 3 and 4 than native-born, and these trajectories were also associated with poor mental health in mid-life. Conclusion: Migrants showed more turbulent transitions between labour market states than natives, and more often found in trajectories with long-term instability and labour market exclusion. Furthermore, the risk of mental ill health in mid-life were higher among trajectories more frequent among migrants.